Pozarolnicza działalność gospodarcza rodzin rolniczych - Stolarska, Alicja (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2005)
The paper describes non-agriculture activity of family farms during the period from 1996 to 2000. Factors determining starting non-agriculture activity and crucial barriers are also presented. The research shows. the level of income achieved from non-agriculture activity as well as a significant increase of the share of non-agriculture activity in personal incomes of the family farms.